1999
DOI: 10.1073/pnas.96.6.3035
|View full text |Cite
|
Sign up to set email alerts
|

The Rho-family GTP exchange factor Vav is a critical transducer of T cell receptor signals to the calcium, ERK, and NF-κB pathways

Abstract: Vav is a GTP͞GDP exchange factor (GEF) for members of the Rho-family of GTPases that is rapidly tyrosine-phosphorylated after engagement of the T cell receptor (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
273
1
3

Year Published

2000
2000
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 236 publications
(305 citation statements)
references
References 39 publications
28
273
1
3
Order By: Relevance
“…3A). This result agrees with the observation that TCR-induced activation of receptor-proximal Src-and Syk-family kinases is normal in Vav1-deficient T cells and thymocytes, as is tyrosine phosphorylation of many cellular proteins [10,11,14].…”
Section: Vav1 Is Not Required For the Assembly Of An Issupporting
confidence: 91%
See 2 more Smart Citations
“…3A). This result agrees with the observation that TCR-induced activation of receptor-proximal Src-and Syk-family kinases is normal in Vav1-deficient T cells and thymocytes, as is tyrosine phosphorylation of many cellular proteins [10,11,14].…”
Section: Vav1 Is Not Required For the Assembly Of An Issupporting
confidence: 91%
“…Mice deficient in Vav1 show defective positive and negative selection of thymocytes, consistent with TCR signaling deficits [6,7]. Furthermore Vav1-deficient T cells are defective in TCR-induced proliferation and cytokine synthesis [8][9][10][11]. Analysis of biochemical signaling pathways has shown that in the absence of Vav1, TCR-induced calcium flux, as well as ERK, NF-‹ B and phosphoinositide 3-OH kinase activation are reduced [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Lysates from apoptotic Jurkat T-cells have proven to be a useful system for studying the in vitro activity of caspases (Tan et al, 1997;Cosulich et al, 1997). We therefore wanted to determine whether (1) caspases activated in apoptotic cells can directly cleave Vav1 and (2) determine the caspase cleavage sites in Vav1.…”
Section: In Vitro Cleavage Of Vav1 In Apoptotic Jurkat T-cell Lysatesmentioning
confidence: 99%
“…Vav1 is furthermore important for the reorganization of the cytoskeleton and actin polymerization which contributes to the clustering of TCRs into patches and caps Holsinger et al, 1998). Overexpression of Vav1 stimulates IL-2 expression by activating transcription factors such as NF-kB and by triggering the activity of mitogen-activated protein kinases (MAPKs) (Costello et al, 1999). Phosphorylation and phosphatidylinositol-3,4,5-triphosphate (PIP3) binding of Vav1 activate its GDP/GTP exchange factor (GEF) activity for Rac (Crespo et al, 1997;Han et al, 1998).…”
Section: Introductionmentioning
confidence: 99%